DINAMIKA PENDIDIKAN ANAK PENGUNGSI DI PEKANBARU: TANTANGAN, STRATEGI ADAPTASI, DAN DAMPAK SOSIAL - Irdayanti, Irdayanti; Ramadhani Agusti Nst, Fitria (Jurnal EL-RIYASAH, 2025)
AbstractEducation is a right for every individual in the world, and the state is responsible for providing it. However, this is not the case for refugee children. They face difficult circumstances, making education a low priority in their lives in refugee camps. Indonesia, as a transit country for many refugees, strives to provide these educational opportunities. This study explores the barriers and adaptation strategies faced by refugee children in the formal education process in Pekanbaru. This research used qualitative research methods and a case study approach. Ten informants were interviewed, and several reference sources were downloaded from the Publish of Perish application to fulfill the data requirements. The results indicate four factors hindering the education process of refugee children in Pekanbaru: legal, infrastructure, community, and cultural factors. Three adaptation strategies are implemented in the education of refugee children: general policy, technical services, and program monitoring